Ізометричні вправи як засіб розвитку сили студентів спеціальної медичної групи - Дегтярьова, Ірина Вікторівна; Войда (Алпатова), Алла Анатоліївна; Гасан, Юлія Миколаївна (Видавничий дім "Гельветика", 2022)
Для збереження та зміцнення здоров’я студентської молоді потрібно передбачати раціональне поєднання нових підходів до фізичного виховання. Застосування різноманітних технологій серед студентів, які займаються у спеціальних медичних групах, має важливе значення для зміцнення здоров’я та розвитку особистості. Силові вправи повинні забезпечувати необхідний рівень різнобічної фізичної підготовки студентів з відхиленнями у стані здоров’я. У роботі було досліджено ефективність використання ізометричних вправ для розвитку силових якостей серед студентів спеціальної медичної групи Національного технічного університету «Харківський політехнічний інститут». Покращення силових показників студентів експериментальної групи надало змогу виконувати більшість запропонованих вправ на заняттях з фізичного виховання у повному обсязі, сприяло позитивним змінам в організмі. Ізометричні вправи можна рекомендувати для використання серед студентів з ослабленим здоров’ям.

To preserve and strengthen the health of student youth, it is necessary to provide a rational combination of new approaches to physical education. It is especially important to choose the right sets of exercises for children with health problems. The use of various technologies by students of a special medical group is important for health promotion and personal development. Strength exercises should provide the necessary level of versatile physical training of students with health problems. Isometric exercises are one of the safest methods of strength training. The use of such exercises for children with health problems can be useful in the prevention of diseases and in improving the quality of life in a relatively short period. Isometric exercises act on muscle strength and flexibility, tone, relaxation, and cardiorespiratory system. Regular performance of isometric static exercises allows you to quickly develop muscles, strengthen ligaments and tendons. All this contributes to the development of balance, coordination, and motor skills. In addition, such exercises contribute to the formation of a positive attitude towards their own health and active lifestyle. The article studies the effectiveness of using isometric exercises for the development of strength qualities among students of a special medical group of the National Technical University “Kharkiv Polytechnic Institute”. The improvement of the strength indicators of the students of the experimental group made it possible to fully use most of the proposed exercises in physical education classes and contributed to positive changes in the body. Isometric exercises can be recommended for students with poor health.
Isometric exercises as a means of strength development students of a special medical group
Keywords: ізометричні вправи; студенти; спеціальна медична група; силові якості; фізичне виховання; isometric exercises; students; special medical group; strength qualities; physical education